Pemodelan Percepatan Tanah sebagai Parameter Hazard Gempabumi menggunakan Metode Deterministic Seismic Hazard Analysis di Kota Manado - Lorensia Kainde; Cosmas Poluakan; Alfrie Musa Rampengan; Muhammad Zulkifli (Jurnal FisTa : Fisika dan Terapannya, 2023)
Research has been carried out on modeling ground acceleration as an earthquake hazard parameter in Manado. This study aims to create an earthquake modeling scenario using Deterministic Seismic Hazard Analysis to determine the estimated PGA value and the intensity value of a significant earthquake. This study utilizes the BMKG SHAKEMAP software to determine the PGA value which is then converted into a modified Mercalli intensity value. A total of 13 modeling scenarios were built in this study. The results show that the scenario of significant earthquake modeling in Manado City and its surroundings using the 2018 BMKG catalog input shows varying results. This depends on the earthquake source parameters as well as the distance from the source to the site. Scenario model 10 is the most representative because it has the same intensity value as the June 20, 1991 earthquake. The resulting PGA value shows the area that has the highest PGA in Manado comes from the 3rd model (8.1% g) and the lowest from the model to 12 (1.4 % g). Due to the limited historical intensity data from the catalog, only 8 models out of 13 models were tested for root mean square error verification ranging values from 0 to 0.25.